A detailed chrono-stratigraphical record of canarian dune archives - Interplay of sand supply and volcanism. (December 2020) - Roettig, C-B.; Kolb, T.; Zöller, L.; Zech, M.; Faust, D.
Abstract: The dune sequences of Fuerteventura mainly consist of biogenic carbonate sands which originate from the shallow marine shelf. By onshore winds those carbonate sands migrate landwards, building up sequences of different dune generations with intercalated reddish silty layers. Former studies discussed the formation of dune generations on Fuerteventura against climatic shifts, sea level changes or changing wind directions, and the more researchers just focused on the volcanism of that island but the influence of volcanism on the formation of dune archives has never been discussed. According to this, the absence of sand deposits is not always climatically controlled nor by sea level changes nor by changing wind direction. The distribution and dating (sharding and OSL dating) of deposits on northern Fuerteventura indicate that the palaeo dune fields close to the western coast were cut off from sand supply gradually, caused by different periods of volcanism. For northern Fuerteventura three main periods can be differentiated: I. Period: around 180–170 ka, II. Period: around 135 ka and III. Period: not later than 50 ka. In that course, we investigated a palaeo dune field close to the eastern coast to illustrate exemplarily the impact of volcanic activity on dune field formation and its morphology. Additionally, we aimed to extend the chrono-stratigraphic correlation of dune sequences (according to Roettig et al., 2017). Now, the correlation across the island is spanning from the western to the eastern coastline and dates back to 450 ka. In terms of luminescence dating, the layers dominated by carbonate sands show only small amount of datable minerals, whereas the material of reddish silty layers are dominated by the imprint of Saharan dust and therefore contain increased content of quartz and feldspar. In contrast to material dominated by carbonate sands the dating performed on palaeosurface material seem to reveal uniformly younger IRSL ages. Highlights: The deposits indicate that the palaeo dunes were cut off from sand supply gradually, associated to three volcanism periods. Three periods can be differentiated: I. around 180–170 ka, II. around 135 ka and III. no later than 50 ka. The stratigraphic correlation across the island (from the western to the eastern coastline) dates back to 450 ka. Dating performed on palaeosurface material seem to reveal uniformly younger IRSL ages (in contrast to sandy layers).